O uso do adobe em Pirenópolis/GO: difusão, descontinuidade, manutenção e ressurgência - Giana Flores da Rocha (2023)
Earth architecture is one of the oldest expressions of human capacity to shape the environment, valuing local resources and adapting to social and environmental needs. Throughout history, these constructions have maintained a fundamental role in expressing the cultural identity of diverse societies. In Brazil, the use of earth as a building material has gone through different phases, from its diffusion to its abandonment and subsequent rescue. Although the abandonment of earth construction in the past is a broad theme, its continuity and rescue are linked to local factors, including socioeconomic, cultural, environmental, and technological issues. This research aims to present and discuss the transformations in the context and technology associated with the use of adobe in Pirenópolis, from the perspective of active adobe producers in the town today. Pirenópolis is a historic town located in the state of Goiás, where adobe is a representative element of local culture. In recent decades, this town has experienced a growing tourism process, driven by its preserved natural and cultural heritage, in which adobe is exploited as a tourism asset. In parallel, the emergence of the Ecocentro IPEC in the 1990s influenced the revitalization of adobe use, inspiring new generations to preserve this construction technique. However, despite the recent recognition of adobe, its valuation does not necessarily reflect the contemporary construction preferences of local residents. The analysis covers the integration of this construction technique into local culture, its subsequent abandonment and discontinuity, when, as part of the urban landscape, it became predominantly associated with tourism and the built heritage of the town. Finally, in contemporary times, we observe a renewed recognition and rescue of this ancient vernacular tradition, marked by various contradictions. The investigation explores the technical, economic, environmental, cultural, and social dimensions that influence the diffusion, discontinuity, maintenance, and resurgence of adobe use in this historic town. To this end, the research is based on theories from the field of vernacular architecture studies and adopts an interdisciplinary methodological approach, seeking to follow the teachings of ethnography, such as the use of field notebooks, the practice of participant observation, attention to informal dialogues, and conducting in-depth interviews with people who experience the researched universe, especially active adobe producers in Pirenópolis.